If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3 + v) = 4v + -5 (3 * 2 + v * 2) = 4v + -5 (6 + 2v) = 4v + -5 Reorder the terms: 6 + 2v = -5 + 4v Solving 6 + 2v = -5 + 4v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-4v' to each side of the equation. 6 + 2v + -4v = -5 + 4v + -4v Combine like terms: 2v + -4v = -2v 6 + -2v = -5 + 4v + -4v Combine like terms: 4v + -4v = 0 6 + -2v = -5 + 0 6 + -2v = -5 Add '-6' to each side of the equation. 6 + -6 + -2v = -5 + -6 Combine like terms: 6 + -6 = 0 0 + -2v = -5 + -6 -2v = -5 + -6 Combine like terms: -5 + -6 = -11 -2v = -11 Divide each side by '-2'. v = 5.5 Simplifying v = 5.5
| -1x+21=18 | | u/2+5=-12 | | 3x-51=27 | | -4u-1= | | x+12.25=19.08 | | 6(3x-6)=-6(k+7) | | 128=8(2+2x) | | x*X=32.5 | | 2m^2+5m-8=0 | | 3-7(x-9)= | | 4x+20=1-7x+14 | | 4t-2=5t+20 | | -23=7-5a-5a | | 400x+300=300x+250 | | 2(3t+-8)-4t=10 | | -6t+-6=0 | | 4x+20=1-7x-14 | | 7-7k=6k+7 | | -2(4+2n)+3= | | 7(n-7)-5(2n+3)=8-3n+8n | | 9x+4y=1 | | 3y-9=y-9 | | 3x+5(x-1)=19 | | 26x+15-9x-6= | | (4xy)(5x^4y)= | | 8x+7=8(x+7) | | 4(a+b)=-16 | | -8x=-6x+30 | | -x^2+2x+20=0 | | 2x-2-12=0 | | 12x=-13y-21 | | -1=-4y+2(y-2) |